Aortitis as a Rare Cause of Aortic Aneurysm and Valve Regurgitation: Is Repair Precluded?. (13th February 2018) - Porras, Carlos; Sanchez-Espin, Gemma; Such, Miguel; Sánchez-Ramos, Jesús; Bautista-Pavés, Alicia; Martín-de la Fuente, Pilar; Ruiz, Josefa; Ortego-Centeno, Norberto; Rodríguez-Bailón, Isabel; Melero, José María
Abstract : Aortitis is an infrequent cause of aortic root dilatation and aortic valve regurgitation. Valve-sparing procedures have been proposed, but there is not clear evidence of which is the treatment of choice. We report the case of a 38-year-old pregnant lady with a diagnosis of idiopathic aortitis associated with aortic root aneurysm and severe aortic valve regurgitation.